Correction systems of the Bender Visual-Motor Gestalt Test: A systematic mapping of the literature - Porto Noronha, Ana Paula (2020)
Background: the Bender test, developed by Lauretta Bender, is intended to evaluate children’s perceptual maturity. Because the instrument lacks a standardized correction system, other researchers have designed different systems for this purpose at distinct periods. Objective: for the present research, we reviewed articles that included the Bender test to identify the most widely used correction systems. Method: eligibility criteria included the instrument application in children up to 10 years of age, focusing on evaluating cognitive aspects. Searches were carried out through the CAPES periodicals portal, which covers both Brazilian and international databases. Results: at the end of the search, 72 published articles were selected and analyzed in their entirety. The four most widely used correction systems were the Koppitz System, Gradual Scoring System, Qualitative Classification System, and Global Classification System. Brazil, Peru and the United States were the countries with the highest number of studies. The predominant objectives were the evaluation of the psychometric properties of correction systems and the use of the Bender test to predict possible learning difficulties, especially in reading and writing. Conclusion: suggested prospects for future Bender test studies are reviews of studies developed with an emotional focus, and the addition of other research databases. Authorship Contribution APPN: conception and design of the study and final revision of the manuscript. AAAS: conception and design of the study and final revision of the manuscript. FJMR: conception and design of the study and final revision of the manuscript. FO: conception and design of the study, search and selection of articles, interpretation of data, discussion and final revision of the manuscript. ASF: conception and design of the study, search and selection of articles, interpretation of data, discussion and final revision of the manuscript. ARLC: conception and design of the study, search and selection of articles, interpretation of data, discussion and final revision of the manuscript. ACZ: conception and design of the study, interpretation of data, discussion and final revision of the manuscript. ADSAJ: conception and design of the study, interpretation of data, discussion and final revision of the manuscript.